(3GdaJf hGdedGMes - (3ESeGYjd Hf YeQ Hf cKjQ Hf Vqh Hf OQY GdbQTj GdHUQhj Ke GdOeTbqj, CHh GdaOGA, YeGO GdOjf,J (B774 (3g` s
(3ChdgG (B:s
(3GdMeO ddg , hSdGe Ydi YHGOg GdPjf GUWai s
(3BNQgG (B:s
(3gPG cJGH GdaJf hGdedGMe GdhGbYI ai BNQ GdReGfMOjK PgH MSf GdNdb HNjQ GdOfjG hGdBNQI s
(3fgGjI cJGH GdHOGjI hGdfgGjI ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B320 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B283s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B194 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2594) s
Keywords: (3GdJGQjNs